Risk factors associated with refractive error among medical students - Kumar, Neelam; Jangra, Babita; Jangra, Mahavir Singh; Pawar, Neeraj (International Journal Of Community Medicine And Public Health, 2018)
Background: Refractive error may be defined as a state in which the optical system of the non-accommodating eye fills to bring parallel rays of light to focus on the retina. Myopia is the most common type of RE, a complex trait including both environmental and genetic factors. Refractive errors are extremely common in the young academically active population. As for any nation they are the features of hardcore human resource, it has huge economic impact. These are the major cause of mild to moderate visual impairment in young individuals; knowledge of the prevalence of refractive error would be helpful in planning of public health strategy. Methods: The present study was carried out on MBBS students studying in 2nd year to 4th year at Pt. BDS PGIMS Rohtak, Haryana. The study was a case – control type of study, in which a total of 100 cases and 100 controls were taken by simple random sampling by lottery method. Cases and controls were matched for age with a difference of ±2 years. Results: Refractive error was found statistically significant among females, students spending more reading hours, watching television, mobile use, inadequate light and family history of refractive error. Means age of refractive error was 14.46±3.4 years. Conclusions: As most of the risk factors are modifiable, so this data could help health care professionals to develop targeted refractive error control policies for the population of students in medical field & insure the policies are more rational, useful, and effective.